Impact of risk factors on cosmetician health - Stankevič, Justina; Gierasimovič, Zita (Slauga. Mokslas ir praktika, 2020)
Qualitative beauty services depend on working conditions in which emotional stress and monotony of work are frequent risk factors, which determine a decrease in the beautician’s work efficiency and cause health disorders. The aim of the investigation was to study the risk factors that have an impact on the beautician’s health. The investigation was carried out in March 2018; as many as 110 specialists, who provide beauty services, chosen at random from seven Lithuanian cities, took part in the investigation. After carrying out the investigation it turned out that the majority of research subjects gave priority to such psycho-social factors as emotional stress, responsibility for the decisions taken, the ergonomic work zone and work organisation. More than a half (30.0 %) of research subjects would agree to change their workplace, and more than one third of the research subjects feel lonely at work due to interpersonal conflicts, and 38.2 % experience emotional exhaustion; 6.36% (n=7) of the research subjects meet with accidents at work. Conclusions: due to the intensity of work half of the research subjects suffer from health disorders: they have swollen feet, feel pain behind their eyes. Due to monotonous work, long working hours, and an unsuitable workplace one third of the research subjects have backache and pain in their transverse humeral ligament. More than a half of the research subjects assess regular rest breaks in the positive.